Strengthening the Bridge Between Academic and the Industry Through the Academia-Industry Collaboration Plan Design Model - Ahmed, Farah; Fattani, Muhammad Tahir; Ali, Syed Rizwan; Enam, Rabia Noor (Frontiers in Psychology, 2022)
The study has been undertaken to integrate two different aspects of the Triple Helix model namely universities and industries. Special attention is given to the prevailing difference between the two hamperings their working as a coherent unit. Integrating the existing knowledge, the study has been proposed through Academia-Industry Collaboration Plan (AICP) design model. The model comprises processes, methods or approaches, and tools. Processes serve as a road map to third parties for establishing collaboration between academia and industry. It has all the essential process models and a series of steps that help minimize the organizational complexity of the collaboration process between academia and industry. Methods or approaches serve the purpose of implementing those processes effectively. Finally, the selection of appropriate tools to integrate possible collaboration improvements that lead to innovation